IMPLEMENTASI SISTEM PELAPORAN PENGGUNAAN DANA PROGRAM SEKOLAH GRATIS TINGKAT SEKOLAH DASAR MENGGUNAKAN METODE ONLINE ANALYTHICAL PROCESSING (OLAP) BERBASIS WEB - Harma Oktafia Linggga Wijaya; Nopalia Nopalia (Jurnal TAM (Technology Acceptance Model), 2017)
This research describes the application of online analysis (OLAP) method in the system of reporting system of use of free school program funding at elementary school level by exploiting technological development. The process of office work today is inseparable from the use of technology as the management of financial data using WEB-based applications will be easier to use because this application is usually opened through all internet browsers. Establishment of a reporting system for the use of free primary school program funding funds by deploying OLAP methods and using PHP and MySQL software.Free school funding during this reporting is felt to be less effective because the manufacture is still using a conventional way that is by using Ms. Office and if there is a mistake then it takes re-making and it also saangat influential in because the distance of one area with the service is still very far therefore the researchers provide solutions using applications that will be made. Metode system development that will be implemented in this research is development method waterfall system, and will also use the design with the Unified Modeling Language Method. In this study will produce media for schools in reporting the use of Free School Program funds to the treasurer. Simplify the treasurer in overseeing the use of Free School Program funds. Providing information on the use of Free School Program funds every quarter and year. With the new PSG funds reporting system faster, precise and accurate and documents can be reprinted.